Suicide Attacks and Religious Cleavages - Andra Filote; Niklas Potrafke; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2015)
Many experts claim that the incidence of suicide attacks is driven by religious cleavages. To test this hypothesis, we investigate whether the total number of suicide attacks per violent conflict or the annual number of suicide attacks per country is associated with simmering religious conflicts. We distinguish between two kinds of religious cleavages: cleavages at the macro level between the stake holders in violent conflicts and cleavages at the micro or battle field level between the actual perpetrators and victims of suicide attacks. Our results do not indicate that religious cleavages are an important precondition for the incidence of suicide attacks.
Keywords: Z12; D74; H56; F51; 330; suicide terrorism; religion; religious cleavages; club goods